Gendering and Degendering: The Problem of Men's Victimization in Intimate Partner Relations in Social and Crisis Workers' Talk. (25th August 2021) - Venäläinen, Satu
Abstract: The notion of intimate partner violence (IPV) as gender-based has been widely questioned by advocates of antifeminist men's rights movements, who have claimed that societal disregard for men's victimization in intimate relations is a central component of discrimination against men in contemporary societies. Similar views have been expressed by researchers as part of a gender-neutral discourse articulated in opposition to feminist, or gender-sensitive, understandings of IPV. To date, the views of helping professionals who work with IPV in terms of men's victimization have been underexplored. This study traces the discursive process of problem construction concerning gender and IPV in social and crisis workers' (N=21) talk about men's victimization through focus group interviews conducted in Finland. The analysis shows that social and crisis workers' sense-making closely aligns with talk about men's victimization by men's rights advocates; they construct and justify men's victimization in intimate relations as a pressing societal concern in ways that both posit gender-specific normative conceptions as a significant, oppressive context for men victims and simultaneously obscure gendered structural inequalities by advocating gender-neutral understandings and solutions for IPV. The analysis highlights challenges in attending to IPV with a gender-sensitive approach in the context of widespread politicization of men's victimization.